2017
DOI: 10.1038/s41598-017-12544-8
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint of local disorder in long range ordered isometric pyrochlores

Abstract: The detailed characterization of local order and disorder in isometric A2B2O7 crystalline pyrochlores is of significant importance in view of their wide range and sensitive technological applications. Nevertheless, much remains to be understood concerning their atomic scale structures. Here we specifically pinpoint local order and disorder in four stoichiometric Ln2Zr2O7 (Ln = La, Nd, Sm and Eu) pyrochlores using a combination of three standard easily available laboratory techniques: XRD, 17O solid-state MAS N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…On increasing the doping level, the main peak IV becomes progressively weaker, while the other peaks become more pronounced, except for the peak at around 380 ppm. No peaks are predicted with a shift similar to this measured signal, consistent with its assignment to a background signal (ZrO 2 or La 2 Zr 2 O 7 ). , The predicted decrease in relative intensity of peak IV (Figure and Figure S27) at higher doping concentrations suggests that this peak may correspond to the 17 O resonances originating from the OLi x sites, whose relative amount decreases upon Al/Ga doping.…”
Section: Resultssupporting
confidence: 77%
“…On increasing the doping level, the main peak IV becomes progressively weaker, while the other peaks become more pronounced, except for the peak at around 380 ppm. No peaks are predicted with a shift similar to this measured signal, consistent with its assignment to a background signal (ZrO 2 or La 2 Zr 2 O 7 ). , The predicted decrease in relative intensity of peak IV (Figure and Figure S27) at higher doping concentrations suggests that this peak may correspond to the 17 O resonances originating from the OLi x sites, whose relative amount decreases upon Al/Ga doping.…”
Section: Resultssupporting
confidence: 77%
“…In our analysis, we assume that the cation distribution induced by the irradiation is essentially frozen into place at the temperatures of interest while the oxygen defects (beyond oxygen Frenkel pairs, which can be viewed as defects that describe anion disorder), having orders-of-magnitude higher mobility, anneal out, and the oxygen adjusts to that cation structure. 46 It has been reported that local disorder occurs in materials that are nominally of pyrochlore structure, 28 that local order can exist in disordered materials (and vice versa), 8,[29][30][31][32] and also that irradiation can induce local disorder within an otherwise ordered structure. 33,34 As XRD only provides average structural information, transmission electron microscopy (TEM) was utilized to examine crystallinity as a function of lm depth in cross-sections of irradiated lms in order to further investigate the nature of the irradiation-induced disorder.…”
Section: Resultsmentioning
confidence: 99%
“…The three most common routes to induce the ODT are via increasing temperature, the difference in the cation radii, and nonstoichiometry [59]. First, most rare earth zirconate and hafnate pyrochlores undergo temperature-induced disordering transition at ≥ 1600℃ [60].…”
Section: Pyrochlore Vs Fluorite and Order-disorder Transition (Odt)mentioning
confidence: 99%
“…Second, the ordered pyrochlore structure is preferred if the size difference between the A-and B-site cations is significant, while the disordered fluorite structure is preferred if the cations are of similar radii. Here, the critical radius ratio for the ODT is approximately 1.46 (disordering if 46), where the radii of the A-and B-site are assumed to be eight-and sixcoordinated [50,59]. Third, non-stoichiometry arising from an imbalance in the concentration of A-and B-site cations, of the form 𝐴 2±𝑦 𝐵 2±𝑦 𝑂 7±𝛿 , can induce an ODT.…”
Section: Pyrochlore Vs Fluorite and Order-disorder Transition (Odt)mentioning
confidence: 99%